Results of the fight against smuggling in Colombia (2015-2016) (2017)
Using as a primary source the reports of the Audit Management Department of the Customs Inspection Management Branch of the National Tax and Customs Office (DIAN) of Colombia an empirical study of the ex post facto, transversal, exploratory and descriptive, presenting the main results of the coordinated action of such as the Dian, the Fiscal and customs police, highway police, state intelligence, national navy and prosecutor 2015 and 2016, against the fight against smuggling.